How to Write Reports and Proposals : Create attention-grabbing documents that achieve your goals - Forsyth, Patrick (Creating success series)
How to Write Reports and Proposals is essential reading for achieving effective writing techniques. Getting a message across on paper and presenting a proposal in a clear and persuasive form are vital skills for anyone in business, and this book provi